2025: status of cardiac xenotransplantation including preclinical models - Byrne, Guerard W.; McGregor, Christopher G. A. (Frontiers in Transplantation, 2025)
Xenotransplantation offers an opportunity to radically change the availability of organs for life-saving human transplantation. Great progress has been made in porcine donor genetic engineering to reduce the immunogenicity of pig organs and potentially enhance their resistance to antibody-mediated rejection. There is also growing insight into more effective immune suppression regimens. These advances have improved the duration of cardiac xenograft survival in non-human primates over the last decade and supported the recent approval of the first-in-human clinical use of pig hearts and kidneys for transplantation. This review critically examines preclinical and clinical results in cardiac xenotransplantation. We identify challenges that remain to achieve consistent and durable clinical graft survival. We discuss the relative value of preclinical non-human primate and human decedent transplant models to optimize patient cross-matching, immune suppression, postoperative monitoring, and graft survival.